Subtelomeric FISH analysis in 76 patients with syndromic developmental delay/intellectual disability - Faravelli Francesca; Pierluigi Mauro; Messa Jole; Molinatto Cristina; Biamino Elisa; Belligni Elga F; Zuffardi Orsetta; Ferrero Giovanni B; Silengo Margherita (BMC, 2009)
Abstract Background Intellectual disability affects approximately 1 to 3% of the general population. The etiology is still poorly understood and it is estimated that one-half of the cases are due to genetic factors. Cryptic subtelomeric aberrations have been found in roughly 5 to 7% of all cases. Methods We performed a subtelomeric FISH analysis on 76 unrelated children with normal standard karyotype ascertained by developmental delay or intellectual disability, associated with congenital malformations, and/or facial dysmorphisms. Results Ten cryptic chromosomal anomalies have been identified in the whole cohort (13,16%), 8 in the group of patients characterized by developmental delay or intellectual disability associated with congenital malformations and facial dysmorphisms, 2 in patients with developmental delay or intellectual disability and facial dysmorphisms only. Conclusion We demonstrate that a careful clinical examination is a very useful tool for pre-selection of patients for genomic analysis, clearly enhancing the chromosomal anomaly detection rate. Clinical features of most of these patients are consistent with the corresponding emerging chromosome phenotypes, pointing out these new clinical syndromes associated with specific genomic imbalances.